Pyelonephritis in pregnancy: «traditional» drainage tactics and its results - V. V. Levchenko; P. P. Morgun; A. V. Voldokhin; A. Y. Abu Trabi; A. S. Maslovsky (Вестник урологии, 2020)
Introduction. Urinary tract drainage for pyelonephritis in pregnancy (PiP) is a topic that is rarely covered in the literature. Available sources are based on personal experience and personal opinions of researchers. In this way, a wide range of tactical decisions is born in such conditions.Purpose of the study. To evaluate the effectiveness of the «traditional» draining treatment tactics for pyelonephritis in pregnant women.Materials and methods. The study included 124 cases of PiP with dilatation of the pyelocaliceal system. Signs of urolithiasis and congenital malformations of the upper urinary tract have not been identified. The average age of the patients was 25 (15–40) years. PiP in the first trimester was diagnosed in 11.3% of women, in the second trimester is in 57.3%, in the third trimester is in 31.4%. In 60.5% of cases, a right-sided PiP was observed, in 24.2% is a left-sided PiP, and in 16.1% it was bilateral PiP. Assessment of dilatation of the upper urinary tract revealed a slight and moderate hydronephrosis in 94.4% of patients, and significant in 5.6%. During treatment, all patients underwent stenting of the ureters. Scheduled stent replacement was performed 6–8 weeks after the initial stenting or drainage replacement. Conversion to percutaneous puncture drainage was required in 4 (3.3%) patients.Results. The early draining tactics of PiP was accompanied by a relatively rapid relief of hyperthermia (96.8% within 3 days) and leukocytosis (88.7% of patients within 4 days). The average hospital bed day for PiP was 4.6. 77.4% of patients required stent replacement during gestation. Stent-associated symptoms of varying severity were noted by 74% of women. Recurrent attack of pyelonephritis under stent drainage was observed in 19.4% of patients, the development of septicemia in 6.5%. In 5.7% of patients, a re-development of the pyelonephritis` attack was noted after removal of the internal drainage stent up to 2 months after delivery. Information was available on the birth and condition of the child at birth for 119 women. Delivery in term was observed in 89.5% of patients, premature spontaneous birth in 10.5%, of which with provocation of labor in 8.9%, with termination of pregnancy for medical reasons in 1.6% (development of preeclampsia, progression of the sepsis phenomena). Self-abortion, intrauterine fetal death or stillbirth was not observed in any woman.Conclusion. The relatively rapid relief of hyperthermia, leukocytosis, a short period of inpatient treatment, the absence of fetal death cases, maternal and infant mortality positively characterize the «traditional» draining tactics. At the same time, a high percentage of the frequency of the preterm delivery threat, maintenance therapy on the stent (16.1%), recurrent attacks of pyelonephritis in drainage conditions (19.6%) during gestation, and also after stent removal in the postpartum period (5.7%), other variations of stent-associated symptoms and complications create the basis for reflection, the search for more optimal tactical and therapeutic approaches.